2017
DOI: 10.1051/0004-6361/201629139
|View full text |Cite
|
Sign up to set email alerts
|

A large sample of Kohonen selected E+A (post-starburst) galaxies from the Sloan Digital Sky Survey

Abstract: Context. The galaxy population in the contemporary Universe is characterised by a clear bimodality, blue galaxies with significant ongoing star formation and red galaxies with only a little. The migration between the blue and the red cloud of galaxies is an issue of active research. Post starburst (PSB) galaxies are thought to be observed in the short-lived transition phase. Aims. We aim to create a large sample of local PSB galaxies from the Sloan Digital Sky Survey (SDSS). Another aim is to present a tool se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 105 publications
2
22
0
Order By: Relevance
“…Regarding gas consumption, several studies have shown that post-starburst galaxies retain a considerable molecular (French et al 2015;Rowlands et al 2015;Alatalo et al 2016;Suess et al 2017;Smercina et al 2018) and atomic (Buyle et al 2006;Zwaan et al 2013) gas reservoirs. Since a significant fraction of post-starbursts seem to be related to late stage mergers (Zabludoff et al 1996;Goto 2005;Meusinger et al 2017;Pawlik et al 2018) their substantial gas reservoirs indicate that the gas remains even after an interactioninduced starburst is complete. Finally, since 40 per cent of earlytype galaxies have been shown to maintain significant molecular gas reservoirs (e.g.…”
Section: Do Galaxy Mergers Lead To Quenching?mentioning
confidence: 99%
“…Regarding gas consumption, several studies have shown that post-starburst galaxies retain a considerable molecular (French et al 2015;Rowlands et al 2015;Alatalo et al 2016;Suess et al 2017;Smercina et al 2018) and atomic (Buyle et al 2006;Zwaan et al 2013) gas reservoirs. Since a significant fraction of post-starbursts seem to be related to late stage mergers (Zabludoff et al 1996;Goto 2005;Meusinger et al 2017;Pawlik et al 2018) their substantial gas reservoirs indicate that the gas remains even after an interactioninduced starburst is complete. Finally, since 40 per cent of earlytype galaxies have been shown to maintain significant molecular gas reservoirs (e.g.…”
Section: Do Galaxy Mergers Lead To Quenching?mentioning
confidence: 99%
“…Though all of these studies could be pointing to low-luminosity AGNs being present, none are definitive. Meusinger et al (2017) studied a large sample of E+A galaxies, finding a slightly elevated number of luminous (> 10 23 W) 1.4 GHz continuum sources and enhanced fraction of mid-IR WISE selected (Assef et al 2013) AGNs, and confirmed the rising mid-IR SED discussed by Melnick & De Propris (2013), but concluded while E+A galaxies do not host strong AGNs, they may contain obscured and/or low-luminosity AGNs or require significant emission from post-AGB stars (as discussed in §3.2.2).…”
Section: Agns In Post-starburstsmentioning
confidence: 99%
“…Amid this new set of deep imaging surveys, the IAC Stripe 82 Legacy Survey is playing a significant role (see e.g. Meusinger et al 2017;Trujillo et al 2017; Román & Trujillo 2017a,b;Peters et al 2017).The IAC Stripe 82 Legacy Survey is a new co-addition of the SDSS Stripe 82 data (Abazajian et al 2009), especially reduced to preserve the faintest surface brightness features of this data set. The survey maps a 2.5 degree wide stripe along the Celestial Equator in the Southern Galactic Cap (-50 • < R.A. < 60 • , -1.25 • < Dec.< 1.25 • ) with a total of 275 square degrees in all the five SDSS filters (u,g,r,i,z).…”
mentioning
confidence: 99%
“…Amid this new set of deep imaging surveys, the IAC Stripe 82 Legacy Survey is playing a significant role (see e.g. Meusinger et al 2017;Trujillo et al 2017; Román & Trujillo 2017a,b;Peters et al 2017).…”
mentioning
confidence: 99%